2021
DOI: 10.1111/bju.15498
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric magnetic resonance imaging of the prostate underestimates tumour volume of small visible lesions

Abstract: To assess the relationship between the volume of the index lesion (IL) measured at multiparametric magnetic resonance imaging (mpMRI; MRIvol) and at radical prostatectomy (RPvol), stratifying it according to Prostate Imaging-Reporting and Data System (PI-RADS) score. Patients and MethodsWe identified 332 men with a positive mpMRI (single lesion with PI-RADS ≥3) who underwent systematic plus targeted biopsy and subsequent RP at two tertiary referral centres between 2013 and 2018. All mpMRIs were reviewed by exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…21,22 Furthermore, other studies reported an underestimation of MRI regarding the true size and extend of PCa tumor. 23,24 Since the ability of MRI to improve prediction of upgrading and/or upstaging is still under debate, other clinical tools, such as PSMA PET/CT scans or biomarkers (the prostate health index, urine PCA3, 4Kscore, TMPRSS2-ERG, and ConfirmMDX) may prove of value. 25,26 Moreover, despite novel findings, these tools still have to prove their efficacy and are not currently available in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Furthermore, other studies reported an underestimation of MRI regarding the true size and extend of PCa tumor. 23,24 Since the ability of MRI to improve prediction of upgrading and/or upstaging is still under debate, other clinical tools, such as PSMA PET/CT scans or biomarkers (the prostate health index, urine PCA3, 4Kscore, TMPRSS2-ERG, and ConfirmMDX) may prove of value. 25,26 Moreover, despite novel findings, these tools still have to prove their efficacy and are not currently available in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Diamand et al failed to identify added benefit from MRI findings regarding prediction of extracapsular extension and seminal vesicle invasion, according to results recorded in an external validation cohort 21,22 . Furthermore, other studies reported an underestimation of MRI regarding the true size and extend of PCa tumor 23,24 . Since the ability of MRI to improve prediction of upgrading and/or upstaging is still under debate, other clinical tools, such as PSMA PET/CT scans or biomarkers (the prostate health index, urine PCA3, 4Kscore, TMPRSS2–ERG, and ConfirmMDX) may prove of value 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mpMRI images were scored and reported using the PI‐RADS version 2 16 . All patients underwent both TBx and SBx at our center according to the technique previously described 17–19 . TBx was performed using a software‐registration fusion approach and was immediately followed by additional random SBx using a sextant biopsy scheme during the same session, in accordance with the currently available guidelines 11 .…”
Section: Methodsmentioning
confidence: 99%
“…16 All patients underwent both TBx and SBx at our center according to the technique previously described. [17][18][19] TBx was performed using a softwareregistration fusion approach and was immediately followed by additional random SBx using a sextant biopsy scheme during the same session, in accordance with the currently available guidelines. 11 Biopsies were performed by experienced urologists using an 18-gauge needle and a biopsy gun providing a specimen size of 18−22 mm.…”
Section: Mpmri and Biopsy Techniquementioning
confidence: 99%